The church of Santos Juanes as a cohesive element of the market district of Valencia – Spain - Molines Cano, José Miguel; Almerich Chulia, Ana Isabel; Llinares Millán, Jaime (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The study of a factory full of history, its peculiarities and the evidence of a building with characteristics that make it unique, encourage a constructive and urban analysis of the Church of Santos Juanes in Valencia (Spain). It has been the scene of numerous events due to its important commercial position. Therefore, without leaving aside the rest of the particularities that have happened to the building and that largely define its personality and its current configuration, this work intends to attend to the rest of the features that fix its character and that allow it to be framed in a specific place inside the city. This article aims to discern and analyze the constructive evolution that the temple has had from its origins to the present, specifying each one of the interventions and relating them to the responsible historical premises, as well as the consequences that they have had in the urban environment that surrounds.